P15 Concerns about corticosteroids among people with asthma: implications for clinical interventions. (16th November 2010) - Cooper, V; Metcalf, L; Upton, J; Walker, S; Versnel, J; Horne, R
Abstract : Introduction and Objectives: Despite the effectiveness of inhaled and systemic corticosteroids in controlling and preventing asthma exacerbations, suboptimal rates of adherence to treatment have been well documented. Previous studies have highlighted the importance of patients′ beliefs about their medicine in determining their adherence to inhaled corticosteroids. The aim of this study was to examine in-depth people′s concerns about inhaled and systemic corticosteroids for asthma and their relation to treatment adherence, and to assess the use of and satisfaction with available sources of information about corticosteroids to inform the development of interventions to support patients. Method: Validated questionnaires measuring concerns about steroid inhalers and tablets (Beliefs about Medicine Questionnaire), satisfaction with information (Satisfaction with Information about Medicines Scale) and adherence (Medication Adherence Report Scale) were sent to Asthma UK members or completed online via the Asthma UK website. Results: 2659 people returned questionnaires. Respondents reported a range of concerns about steroid medicines. The most prevalent concerns about steroid inhalers were about potential long-term effects (60%) side effects (sore throat or oral thrush (43%); effects on the voice (37%)) and becoming dependent on the inhaler (36%). The most prevalent concerns about steroid tablets were about long-term effects (81%), side effects (concerns about weight gain (66%); weakened bones (65%)) and general worry about taking the tablets (62%). People had stronger concerns about steroid tablets compared to steroid inhalers (p<0.0001). Concerns about treatment were associated with lower adherence to steroid inhalers (p<0.0001) and steroid tablets (p<0.0001). The most frequent sources of information used by people to address their concerns were reading the patient information leaflet and consulting nurses and doctors. Two-thirds of the sample indicated that they were dissatisfied with the information they had received about steroid treatments. Conclusion: People with asthma had a range of concerns about steroid medicines which impacted negatively on adherence. For many, treatment concerns had not been alleviated by the available information sources. Developing and implementing interventions that address patients′ concerns about the side effects of corticosteroids may improve adherence to asthma treatment and improve asthma control.